The Development of Metabolic Risk Factors After the Initiation of the Second Line Anti- Retroviral Therapy - Mittal, Apoorva (JCDR Research and Publications (P) Limited, 2013)
Background and objective: A Highly Active Anti-Retroviral Therapy (HAART) is accompanied with several metabolic effects like adipose redistribution and insulin resistance. In this study, we evaluated the association between a HAART and lipodystrophy. Methods: A cross sectional study, whose subjects were Human Immunodeficiency Virus (HIV) infected patients, was conducted at a tertiary care hospital in south India. Among these, 27 were on protease inhibitors for at-least 6 months and 13 were drug naive patients. The assessments of lipodystrophy, fasting blood sugar and the fasting lipid profile were done and these parameters were compared in the two groups. Results: The analysis of the data which was collected, showed an elevation in the total cholesterol levels in the individuals who were on the protease inhibitors versus the drug naive patients. There was a significant elevation in the Low Density Lipoprotein (LDL) cholesterol levels and a decrease in High Density Lipoprotein (HDL) cholesterol levels in the individuals who were on protease inhibitors. It was also observed that the HDL cholesterol levels decreased with an increase in the duration of the therapy. The LDL cholesterol levels increased with the duration of the therapy. Conclusion: The human immunodeficiency virus infection is itself related to the metabolic complications which are aggravated on the use of second line anti retroviral therapy. Therefore, after initiating the treatment with protease inhibitors, a periodic evaluation of the serum lipid levels and the blood sugar profile should be done as a standard care.